School Principal Leadership Management in Improving Emotional Intelligence of Islamic Secondary School Students - Rokimin, Rokimin; Manaf, Sofwan; Akhirudin, M. Towil (Management of Education: Jurnal Manajemen Pendidikan Islam, 2025)
This study analyzes the principal's leadership management in enhancing students' emotional intelligence (EQ) at MTs Darunnajah. Emotional intelligence is a crucial aspect of education, contributing to academic achievement, social skills, and character building. In Islamic education, EQ is a foundation for developing morally upright individuals capable of facing academic and social challenges. The researcher employed a qualitative descriptive approach and collected data through in-depth interviews with the principal, teachers, students, and parents, supported by observation and documentation of school activities. They analyzed the data using thematic coding, applied source triangulation, and validated the findings through member checking to ensure credibility. The study found that the principal developed students' EQ through four core managerial functions: planning, organizing, implementing, and supervising. The principal created systematic planning that provided clear direction for school programs and organized collaborative efforts among teachers to integrate character values into every lesson. The implementation aligned with the school's vision and mission by emphasizing character-based learning and empathy-building activities. The principal also supervised the process to evaluate program effectiveness and make necessary improvements. In addition to leadership management, internal factors such as emotional regulation and self-motivation contributed to students' EQ development. In contrast, external factors included parental support, teacher role modeling, and an inclusive school climate. In conclusion, the principal's effective and collaborative leadership fostered a supportive learning environment that enhanced students' EQ. Sustainable development of emotional intelligence requires continuous synergy among principals, teachers, and parents.